2011
DOI: 10.1007/s12034-011-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

XRD spectra of new YBaCuO superconductors

Abstract: XRD spectra of new YBaCuO superconductors were studied. There were 2 phases found in our samples, the superconducting phase and the non-superconducting phase. The more non-superconducting phase, the more anisotropy parameters were found. The amount of impurities have no effect on the value of c-axis which has a linear relation to the number of Cu-atoms. So the new formula of YBaCuO are the new types of superconductor in this family that have higher c-axis than the Y123.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The results of line fitting demonstrated that α = 3 shows a more appropriate fit to the curves. Also, the slight difference between α = 2 and 3 suggests that the system we studied is two-dimensional [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of line fitting demonstrated that α = 3 shows a more appropriate fit to the curves. Also, the slight difference between α = 2 and 3 suggests that the system we studied is two-dimensional [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 in the study by Udomsamuthirun, et al (2010) shows a linear relation between the number of Cu-atoms in their sample versus the c-axis value in the XRD spectra (Pimentel-Jr, et al, 2015). In our study, figure 4a shows the results found for our samples, which agree with those of Sujinnapram, et al (2011). Figures 4 (b,c) and 5 show a decreasing linear relationship of the orthorhombic unit cell parameter (a, b, V) in function of the rare earth ionic ratio RE 3 Ba 5 Cu 8 O 18 samples ;Tarascón, et al (1987) suggested this is due to the removal of oxygen atoms from the copper atoms.…”
Section: Resultssupporting
confidence: 89%
“…Figures 4 (b,c) and 5 show a decreasing linear relationship of the orthorhombic unit cell parameter (a, b, V) in function of the rare earth ionic ratio RE 3 Ba 5 Cu 8 O 18 samples ;Tarascón, et al (1987) suggested this is due to the removal of oxygen atoms from the copper atoms. From this perspective, the copper that was fourfold coordinated becomes twofold coordinated with an oxygen above and one below (Sujinnapram, et al, 2011). Figure 6 shows the ZFC and FC magnetization curves as a function of the temperature, which is typical of superconducting materials.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results in its surface crystalline products, such as amorphous calcium phosphate (ACP) and octacalcium phosphate (OCP). The impurities introduced during the drying process can muddy the background, but have no effect on the main peak shapes (Sujinnapram et al, 2011).…”
Section: Characterization Analysismentioning
confidence: 99%